(4x+6)-(2x+4)=2x

Simple and best practice solution for (4x+6)-(2x+4)=2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+6)-(2x+4)=2x equation:


Simplifying
(4x + 6) + -1(2x + 4) = 2x

Reorder the terms:
(6 + 4x) + -1(2x + 4) = 2x

Remove parenthesis around (6 + 4x)
6 + 4x + -1(2x + 4) = 2x

Reorder the terms:
6 + 4x + -1(4 + 2x) = 2x
6 + 4x + (4 * -1 + 2x * -1) = 2x
6 + 4x + (-4 + -2x) = 2x

Reorder the terms:
6 + -4 + 4x + -2x = 2x

Combine like terms: 6 + -4 = 2
2 + 4x + -2x = 2x

Combine like terms: 4x + -2x = 2x
2 + 2x = 2x

Add '-2x' to each side of the equation.
2 + 2x + -2x = 2x + -2x

Combine like terms: 2x + -2x = 0
2 + 0 = 2x + -2x
2 = 2x + -2x

Combine like terms: 2x + -2x = 0
2 = 0

Solving
2 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 | | 7log(4x-1)=14 | | 5b-5.25b+3=3.75 | | -4c+5=9 |

Equations solver categories